2018
DOI: 10.1002/lary.27410
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration in children with unilateral vocal fold paralysis

Abstract: Objectives/Hypothesis To describe the prevalence of aspiration in children with unilateral vocal fold paralysis who underwent objective assessment of swallow function. Study Design Retrospective chart review. Methods A study of patients presenting to our institution with unilateral vocal fold paralysis in 2015 was conducted. All patients were diagnosed using flexible laryngoscopy. Patients were included if they underwent at least one modified barium swallow (MBS) study for evaluation of their swallowing functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
2
19
0
1
Order By: Relevance
“…This is consistent with findings from previous studies. 5,12,19,20 Although patients who did not have postoperative VFMI were more likely to have oral phase difficulties and less likely to have airway protection deficits, it is notable that the silent aspiration rate in this group was still 28%. Although the majority of our study's participants were identified with the use of FNL, more recently LUS has been the mainstay for early noninvasive identification of VFMI at our institution.…”
Section: Discussionmentioning
confidence: 84%
“…This is consistent with findings from previous studies. 5,12,19,20 Although patients who did not have postoperative VFMI were more likely to have oral phase difficulties and less likely to have airway protection deficits, it is notable that the silent aspiration rate in this group was still 28%. Although the majority of our study's participants were identified with the use of FNL, more recently LUS has been the mainstay for early noninvasive identification of VFMI at our institution.…”
Section: Discussionmentioning
confidence: 84%
“…Silent aspiration was described in several studies of preterm infants ( 130 132 , 134 ). Those with vocal cord paralysis are at high risk for silent aspiration.…”
Section: Resultsmentioning
confidence: 99%
“…1 Clinicians should recognize the potential for silent aspiration and advocate for feeding evaluations to characterize swallowing mechanics. 22 Undiagnosed left VCP might lead to inappropriate treatment choices and early detection may improve outcomes. 23 Pediatric otolaryngologists caring for these children should strive for a timely and accurate diagnosis of VCP.…”
Section: Discussionmentioning
confidence: 99%